Polarizing plate with retardation layer, its manufacturing method, and image display device using the polarizing plate with retardation layer

JP7636222B2Active Publication Date: 2025-02-26NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021046925
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-02-26
Estimated Expiration
2041-03-22

AI Technical Summary

Benefits of technology

【0006】 本発明の実施形態によれば、高温環境下における反射色相変化が抑制された画像表示装置を実現し得る位相差層付偏光板を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636222000006
    Figure 0007636222000006
  • Figure 0007636222000007
    Figure 0007636222000007
  • Figure 0007636222000001
    Figure 0007636222000001
Patent Text Reader

Abstract

To provide a polarizing plate with a retardation layer which can realize an image display device in which reflection hue change under a high temperature environment is suppressed.SOLUTION: A polarizing plate with a retardation layer according to an embodiment of the present invention comprises: a polarizing plate which includes polarizers and a protective layer in at least one of the polarizers; a first retardation layer which is arranged on the side opposite to the viewing side of the polarizing plate; and a second retardation layer which is pasted to the side opposite to the polarizing plate of the first retardation layer via an adhesive layer. The first retardation layer is the retardation layer other than a C plate and the second retardation layer is the C plate. In one embodiment, the adhesive layer consists of the activation energy ray curable adhesive, and the cure shrinkage of the adhesive is 5% or greater. In another embodiment, the laminated body of the first retardation layer and the second retardation layer is subjected to the annealing treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a retardation layer, a method for producing the same, and an image display device using the polarizing plate with a retardation layer. [Background technology]

[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) have rapidly become widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used. Recently, as the demand for thinner image display devices has increased, the demand for thinner retardation layer-attached polarizing plates has also increased. As one approach to the reduction in thickness of retardation layer-attached polarizing plates, a retardation layer-attached polarizing plate using a retardation layer in which liquid crystal compounds are fixed in an oriented state has been proposed. However, image display devices using such retardation layer-attached polarizing plates have a problem in that the reflection hue changes significantly in high-temperature environments. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-064274 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide a polarizing plate with a retardation layer that can realize an image display device in which change in reflective hue is suppressed in a high-temperature environment. [Means for solving the problem]

[0005] The retardation film - attached polarizing plate according to an embodiment of the present invention includes a polarizing plate including a polarizer and at least one protective layer on at least one of the polarizers, a first retardation film disposed on the side opposite to the viewing side of the polarizing plate, and a second retardation film bonded via an adhesive layer to the side opposite to the polarizing plate of the first retardation film. The first retardation film is a retardation film other than a C - plate, and the second retardation film is a C - plate. In one embodiment, the adhesive layer is composed of an active energy ray - curable adhesive, and the curing shrinkage rate of the adhesive is 5% or more. In another embodiment, the laminate of the first retardation film and the second retardation film is annealed. In one embodiment, the first retardation film exhibits a refractive index characteristic of nx>ny≧nz, Re(550) is 100 nm to 200 nm, and satisfies the relationship of Re(450)<Re(550); the second retardation film exhibits a refractive index characteristic of nz>nx = ny. Here, Re(450) and Re(550) are the in - plane retardations measured with light having wavelengths of 450 nm and 550 nm at 23°C, respectively. In one embodiment, the first retardation film and the second retardation film are alignment - solidified layers of a liquid crystal compound. According to another aspect of the present invention, a method for manufacturing the above - mentioned retardation film - attached polarizing plate is provided. This manufacturing method includes forming the first retardation film on a first substrate, forming the second retardation film on a second substrate, and bonding the first retardation film of the laminate of the first substrate and the first retardation film and the second retardation film of the laminate of the second substrate and the second retardation film via an active energy ray - curable adhesive to form an intermediate laminate. In one embodiment, the curing shrinkage rate of the active energy ray - curable adhesive is 5% or more. In this case, the manufacturing method includes increasing Re(550) of the first retardation film by 0.5 nm or more when forming the intermediate laminate. In another embodiment, the manufacturing method further includes annealing the intermediate laminate. In this case, the manufacturing method includes increasing the Re(550) of the first retardation layer by 0.5 nm or more by the annealing. In one embodiment, the annealing temperature is 80° C. or more, and the annealing time is 1 minute or more. According to yet another aspect of the present invention, there is provided an image display device, the image display device including the above-mentioned retardation layer-attached polarizing plate. Effect of the Invention

[0006] According to the embodiment of the present invention, it is possible to obtain a retardation layer-attached polarizing plate capable of realizing an image display device in which change in reflective hue in a high-temperature environment is suppressed. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a flow chart including schematic cross-sectional views, illustrating a manufacturing process of a retardation layer-attached polarizing plate according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0010] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 in the illustrated example typically includes a polarizing plate 10, a first retardation layer 21, and a second retardation layer 22 in this order from the viewing side. The polarizing plate 10 includes a polarizer 11 and a protective layer disposed on at least one of the polarizers 11. In the illustrated example, protective layers (viewing-side protective layer 12 and inner protective layer 13) are disposed on both sides of the polarizer 11, but one of the viewing-side protective layer 12 or the inner protective layer 13 may be omitted depending on the purpose, etc. The first retardation layer 21 is typically attached to the polarizing plate 10 on the side opposite the viewing side via a first adhesive layer 40. The second retardation layer 22 is attached to the polarizing plate 10 on the side opposite the first retardation layer 21 via an adhesive layer 30.

[0011] In an embodiment of the present invention, the first retardation layer 21 is a retardation layer other than a C-plate, and the second retardation layer 22 is a C-plate. The first retardation layer 21 typically exhibits refractive index characteristics of nx > ny ≥ nz. That is, the first retardation layer can be a positive A-plate (nx > ny = nz) or a negative B-plate (nx > ny > nz). Further, the Re(550) of the first retardation layer is preferably 100 nm to 200 nm, and preferably satisfies the relationship of Re(450) < Re(550). The second retardation layer 22 typically exhibits refractive index characteristics of nz > nx = ny. That is, the second retardation layer can be a positive C-plate. If the first retardation layer and the second retardation layer have such a configuration, a polarizing plate with a retardation layer having excellent antireflection characteristics can be realized.

[0012] The first retardation layer and the second retardation layer are typically an alignment and curing layer of a liquid crystal compound (hereinafter, may be simply referred to as a liquid crystal alignment and curing layer). By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be made significantly larger than that of a non-liquid crystal material, so the thickness of the first retardation layer for obtaining a desired in-plane retardation can be significantly reduced. Also, the second retardation layer (positive C-plate) can be formed with a very thin thickness. As a result, further thinning of the polarizing plate with a retardation layer can be realized. In this specification, the "alignment and curing layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. Note that the "alignment and curing layer" is a concept that includes an alignment and curing layer obtained by curing a liquid crystal monomer. The first retardation layer typically has rod-shaped liquid crystal compounds aligned in the direction of the slow axis of the retardation layer (homogeneous alignment); the second retardation layer typically has rod-shaped liquid crystal compounds aligned perpendicular to the film surface (homeotropic alignment).

[0013] In the embodiment of the present invention, the adhesive layer 30 is made of an active energy ray curable adhesive. The cure shrinkage rate of the adhesive is typically 5% or more. Furthermore / or, the laminate of the first retardation layer and the second retardation layer is typically annealed. With such a configuration, the Re(550) of the laminate of the first retardation layer and the second retardation layer (substantially the first retardation layer) can be made larger than when the cure shrinkage rate of the adhesive is small and / or when the laminate of the first retardation layer and the second retardation layer is not annealed. As a result, the front reflection hue a value and b value of the initial stage (before being placed in a high temperature environment) of the image display device can be made larger than the L * a * b * It is possible to shift the color in the color space chromaticity diagram in advance in the direction in which the color changes in a high-temperature environment. Therefore, the reflection hue change Δa in a high-temperature environment (for example, after a durability test) * b * This effect is remarkable when the retardation layer is a liquid crystal alignment solidified layer. That is, the liquid crystal alignment solidified layer is easily affected by the dimensional shrinkage of the polarizing plate in a high temperature environment, and the reflection hue change Δa can be reduced compared to the retardation layer of a resin film. * b * Here, as described above, by shifting the initial front reflection hue a and b values ​​in advance in the direction in which they change in a high-temperature environment (by exposing the polarizer to the effects of dimensional shrinkage in advance), the effects of dimensional shrinkage of the polarizer in a high-temperature environment can be reduced, and as a result, the reflection hue change Δa * b * can be made smaller.

[0014] For practical purposes, a second adhesive layer is provided on the opposite side of the second retardation layer 22 to the polarizing plate 10 (i.e., as the outermost layer on the opposite side to the viewing side), so that the retardation layer-attached polarizing plate can be attached to an image display panel. Furthermore, it is preferable that a release film (not shown) is temporarily attached to the surface of the second adhesive layer 50 until the retardation layer-attached polarizing plate is used. By temporarily attaching the release film, the second adhesive layer 50 is protected and the retardation layer-attached polarizing plate can be formed into a roll.

[0015] The total thickness of the retardation layer-attached polarizing plate is preferably 120 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less. The lower limit of the total thickness may be, for example, 45 μm. A retardation layer-attached polarizing plate having such a total thickness may have extremely excellent flexibility and bending durability. As a result, the retardation layer-attached polarizing plate may be particularly suitably applied to a curved image display device and / or a bendable or foldable image display device. The total thickness of the retardation layer-attached polarizing plate refers to the total thickness from the viewer-side protective layer 12 (if present) to the second retardation layer 22. That is, the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the second adhesive layer 50.

[0016] The retardation layer-attached polarizing plate may further include other optical functional layers. The type, characteristics, number, combination, arrangement position, etc. of the optical functional layers that can be provided in the retardation layer-attached polarizing plate may be appropriately set according to the purpose. For example, the retardation layer-attached polarizing plate may further have a conductive layer or a conductive layer-attached isotropic substrate (both are not shown). The conductive layer or the conductive layer-attached isotropic substrate is typically provided on the outside (opposite side to the polarizing plate 10) of the second retardation layer 22. When the conductive layer or the conductive layer-attached isotropic substrate is provided, the retardation layer-attached polarizing plate may be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between the image display panel and the polarizing plate. Also, for example, the retardation layer-attached polarizing plate may further include other retardation layers. The optical characteristics (for example, refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the other retardation layers may be appropriately set according to the purpose.

[0017] The polarizing plate with a retardation layer may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently longer than its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, than its width. The long polarizing plate with a retardation layer can be wound into a roll.

[0018] The components of the retardation layer-attached polarizing plate will be described in more detail below.

[0019] B. Polarizing plate B-1.Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0020] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.

[0021] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.

[0022] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0023] The thickness of the polarizer is preferably 15 μm or less, more preferably 12 μm or less, even more preferably 10 μm or less, and particularly preferably 8 μm or less. On the other hand, the thickness of the polarizer is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. If the thickness of the polarizer is in this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0024] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 43.0% to 46.0%, and preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0025] B-2.Protective layer The viewing-side protective layer 12 and the inner protective layer 13 are each composed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the films include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, cyclic olefins (e.g., polynorbornene), polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.

[0026] The retardation layer-attached polarizing plate is typically arranged on the viewing side of an image display device, as described later, and the viewing-side protective layer 12 is arranged on the viewing side. Therefore, the viewing-side protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the viewing-side protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function, imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the retardation layer-attached polarizing plate can be suitably applied to image display devices that can be used outdoors. In addition, preferable examples of materials constituting the viewing-side protective layer include cyclic olefin-based (e.g., polynorbornene-based) and cellulose-based resins (e.g., TAC).

[0027] The thickness of the viewer-side protective layer 12 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm. When a surface treatment is applied, the thickness of the viewer-side protective layer includes the thickness of the surface treatment layer.

[0028] In one embodiment, the inner protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the inner protective layer 13 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm. Preferred materials constituting the inner protective layer include cyclic olefin-based (e.g., polynorbornene-based), cellulose-based resins (e.g., TAC), and acrylic-based resins.

[0029] C. Retardation layer C-1. First retardation layer The first retardation layer 21 can typically function as a λ / 4 plate. The first retardation layer is typically provided to impart antireflection properties to an image display device. The first retardation layer typically exhibits refractive index characteristics of nx > ny ≧ nz as described above. The in-plane retardation Re(550) of the first retardation layer is preferably 100 nm to 200 nm as described above, more preferably 110 nm to 170 nm, and even more preferably 120 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.

[0030] The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, an image display device having a very excellent reflected hue can be obtained.

[0031] The first retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. That is, the first retardation layer preferably satisfies the relationship of Re(450) < Re(550) as described above. The first retardation layer preferably further satisfies the relationship of Re(550) < Re(650). Re(450) / Re(550) of the first retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. Re(650) / Re(550) of the first retardation layer is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1. With such a configuration, very excellent antireflection characteristics can be realized.

[0032] The angle formed between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle is within such a range, by using the retardation layer as a λ / 4 plate as described above, an image display device having very excellent antireflection characteristics can be obtained.

[0033] The first retardation layer can be a liquid crystal alignment solidified layer, as described above. As described above, by using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so the thickness of the first retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As described above, the first retardation layer is typically oriented in a state where the rod-shaped liquid crystal compound is aligned in the slow axis direction of the retardation layer (homogeneous alignment).

[0034] Examples of liquid crystal compounds include liquid crystal compounds whose liquid crystal phase is a nematic phase (nematic liquid crystals). Examples of such liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The mechanism by which liquid crystallinity of liquid crystal compounds is expressed may be either lyotropic or thermotropic. The liquid crystal polymers and liquid crystal monomers may be used alone or in combination.

[0035] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other, thereby fixing the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed first retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the first retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0036] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0037] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, GB2280445, etc. can be used.

[0038] The thickness of the first retardation layer can be set to a thickness that can function appropriately as a λ / 4 plate. The thickness of the first retardation layer is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, it is possible to realize an in-plane retardation equivalent to that of a resin film with a thickness that is significantly thinner than that of a resin film.

[0039] C-2. Second retardation layer As described above, the second retardation layer 22 may be a positive C plate whose refractive index characteristics show the relationship nz>nx=ny. By using a positive C plate as the second retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the thickness direction retardation Rth(550) of the second retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second retardation layer may be less than 10 nm.

[0040] The second retardation layer may be formed of any appropriate material. The second retardation layer is preferably made of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method for forming the retardation layer include the liquid crystal compound and the method for forming the retardation layer described in

[0020] to

[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0041] D.Adhesive layer The adhesive layer 30 is composed of an active energy ray curable adhesive as described above. The cure shrinkage rate of the adhesive is typically 5% or more as described above, preferably 7% or more, more preferably 10% or more, and further preferably 14% or more. The upper limit of the cure shrinkage rate of the adhesive may be, for example, 20%. With such a configuration, the Re(550) of the laminate of the first retardation layer and the second retardation layer (substantially the first retardation layer) can be increased, and the front reflection hue a value and b value at the initial stage (before being placed in a high temperature environment) of the image display device can be increased to L * a * b * It is possible to shift the color in the color space chromaticity diagram in advance in the direction in which the color changes in a high-temperature environment. Therefore, the reflection hue change Δa in a high-temperature environment (for example, after a durability test) * b * In addition, when the laminate of the first retardation layer and the second retardation layer is annealed, even if the cure shrinkage rate of the adhesive is smaller than the above range (for example, 3%), the above-mentioned effect may be obtained.

[0042] As the active energy ray curable adhesive, any suitable active energy ray curable adhesive can be used as long as the curing shrinkage rate can be within the above range. Examples of the active energy ray curable adhesive include ultraviolet ray curable adhesives and electron beam curable adhesives. In addition, from the viewpoint of the curing mechanism, examples of the active energy ray curable adhesive include radical curable adhesives, cationic curable adhesives, anionic curable adhesives, and hybrids of radical curable adhesives and cationic curable adhesives. Typically, radical curable ultraviolet ray curable adhesives can be used. This is because they are highly versatile and the properties (composition) can be easily adjusted.

[0043] The active energy ray curable adhesive typically contains a monofunctional component, a polyfunctional component (curing component), and a photopolymerization initiator. The monofunctional component and the polyfunctional component are typically radical polymerizable compounds. Preferred monofunctional components include, for example, higher alkyl esters of (meth)acrylic acid and modified products thereof. Specific examples include isostearyl acrylate, lauryl acrylate, acryloylmorpholine, and unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone. Preferred polyfunctional components include, for example, monomers and / or oligomers having two or more functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples include polyethylene glycol diacrylate, trimethylpropane triacrylate, and glycerin triacrylate. Specific examples of monofunctional or polyfunctional components other than those mentioned above include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-methylol acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and 9-vinyl carbazole. In one embodiment, the monofunctional or polyfunctional component has a ring structure. Specific examples include acryloyl morpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole. Each of the monofunctional or polyfunctional components may be used alone or in combination of two or more.

[0044] The active energy ray curable adhesive may further contain a cationic polymerizable compound as required. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of the monofunctional cationic polymerizable compound include p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane. Examples of the polyfunctional cationic polymerizable compound include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane. A silane coupling agent may be used as the cationic polymerizable compound. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane.

[0045] The active energy ray-curable adhesive may further contain an acrylic oligomer, if necessary. The molecular weight of the acrylic oligomer may be appropriately set depending on the purpose.

[0046] The active energy ray curable adhesive may further contain a plasticizer (e.g., an oligomer component), a crosslinking agent, a diluent, etc., depending on the purpose. By adjusting the types, combinations, and mixing ratios of these components, as well as the above-mentioned monofunctional component, polyfunctional component, cationic polymerizable compound, acrylic oligomer, and photopolymerization initiator, an active energy ray curable adhesive having a desired cure shrinkage rate can be obtained. Note that each of the above-mentioned components may be a commercially available product.

[0047] The thickness of the active energy ray-curable adhesive after curing is preferably 0.1 μm to 3.0 μm.

[0048] Details of the active energy ray-curable adhesive are described, for example, in JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.

[0049] E. Adhesive layer For the first adhesive layer 40 and the second adhesive layer 50, any appropriate adhesive can be used depending on the purpose, and detailed description thereof will be omitted.

[0050] F. Method for manufacturing a polarizing plate with a retardation layer The embodiment of the present invention also includes the above-mentioned method for producing a polarizing plate with a retardation layer. This method includes forming a first retardation layer on a first base material, forming a second retardation layer on a second base material, and bonding the first retardation layer of the laminate of the first base material and the first retardation layer and the second retardation layer of the laminate of the second base material and the second retardation layer with an active energy ray curable adhesive to form an intermediate laminate. Hereinafter, a representative example of the method will be described with reference to FIG. 2.

[0051] First, as shown in FIG. 2(a), a first retardation layer 21 is formed on a first substrate 61. The first substrate may be any suitable resin film. Specific examples include a cellulose-based resin film such as a triacetyl cellulose (TAC) film, a polyester-based film such as a polyethylene terephthalate (PET) film, and an acrylic resin film. A TAC film is preferable. The first retardation layer may be formed by, typically, performing an orientation treatment on the surface of the first substrate, applying a coating liquid containing a liquid crystal compound to the surface to orient the liquid crystal compound in a direction corresponding to the orientation treatment, and fixing the orientation state. Any suitable orientation treatment may be adopted as the orientation treatment. Specific examples include a mechanical orientation treatment, a physical orientation treatment, and a chemical orientation treatment. Specific examples of the mechanical orientation treatment include a rubbing treatment and a stretching treatment. Specific examples of the physical orientation treatment include a magnetic field orientation treatment and an electric field orientation treatment. Specific examples of the chemical orientation treatment include an oblique deposition method and a photo-orientation treatment. The treatment conditions of the various orientation treatments may be any suitable conditions depending on the purpose. The liquid crystal compound is aligned by treating it at a temperature at which it exhibits a liquid crystal phase according to the type of liquid crystal compound. By carrying out such a temperature treatment, the liquid crystal compound takes on a liquid crystal state, and the liquid crystal compound is aligned according to the alignment treatment direction of the substrate surface. In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by carrying out a polymerization treatment or a crosslinking treatment on the liquid crystal compound aligned as described above. In this way, the first retardation layer 21 is formed on the first substrate 61.

[0052] On the other hand, as shown in FIG. 2(b), a second retardation layer 22 is formed on a second substrate 62. The second substrate may be any suitable resin film. Specific examples are as described above with respect to the first substrate. The second substrate is preferably a PET film. The second retardation layer is formed, for example, as described above, using the liquid crystal compound and forming method described in

[0020] to

[0028] of JP-A-2002-333642. In this manner, the second retardation layer 22 is formed on the second substrate 62.

[0053] Next, as shown in FIG. 2(c), the first retardation layer 21 and the second retardation layer 22 in each of the laminates obtained above are bonded together via an active energy ray curable adhesive to form an intermediate laminate. The active energy ray curable adhesive is as described in the above section D. More specifically, for example, an active energy ray curable adhesive is applied to the surface of the second retardation layer, and the first retardation layer is brought into contact with the surface (typically, bonded together) to form a precursor of the intermediate laminate, and the intermediate laminate is formed by heating as necessary and curing the adhesive by irradiating a predetermined cumulative amount of active energy rays (for example, ultraviolet rays). Here, the curing shrinkage rate of the active energy ray curable adhesive is typically 5% or more as described above. If the curing shrinkage rate is within such a range, the Re(550) of the first retardation layer can be increased by preferably 0.5 nm or more, more preferably 1.0 nm or more, even more preferably 1.5 nm or more, particularly preferably 2.5 nm or more, and particularly preferably 3.0 nm or more due to the shrinkage when the intermediate laminate is formed. As a result, the front reflection hue a and b values ​​of the initial state of the image display device (before being placed in a high-temperature environment) were compared with those of the L * a * b * It is possible to shift the color in the color space chromaticity diagram in advance in the direction in which the color changes in a high-temperature environment. Therefore, the reflection hue change Δa in a high-temperature environment (for example, after a durability test) * b * However, when an annealing treatment described later is performed, the effects of the embodiment of the present invention may be obtained even if the cure shrinkage rate is less than 5%.

[0054] Next, as shown in FIG. 2(d), the intermediate laminate is annealed. The annealing temperature is preferably 80° C. or higher, more preferably 90° C. or higher, even more preferably 95° C. or higher, and particularly preferably 100° C. or higher. The upper limit of the treatment temperature may be, for example, 120° C. The treatment time may vary depending on the treatment temperature. The treatment time is preferably 1 minute or higher, more preferably 3 minutes or higher, even more preferably 7 minutes or higher, and particularly preferably 10 minutes or higher. The upper limit of the treatment time may be, for example, 20 minutes. By performing the annealing treatment, the Re(550) of the first retardation layer can be increased by preferably 0.5 nm or more, more preferably 1.0 nm or more, even more preferably 1.5 nm or more, particularly preferably 2.5 nm or more, and particularly preferably 3.0 nm or more. As a result, the front reflection hue a value and b value of the initial stage (before being placed in a high-temperature environment) of the image display device can be increased by 0.5 nm or more, more preferably ... * a * b * It is possible to shift the color in the color space chromaticity diagram in advance in the direction in which the color changes in a high-temperature environment. Therefore, the reflection hue change Δa in a high-temperature environment (for example, after a durability test) * b * However, when the cure shrinkage rate of the active energy ray curable adhesive is 5% or more as described above, the effect of the embodiment of the present invention may be obtained even without carrying out the annealing treatment.

[0055] Preferably, an intermediate laminate is formed using an active energy ray curable adhesive having a cure shrinkage rate of 5% or more, and the intermediate laminate is subjected to an annealing treatment. As a result, the Re(550) of the first retardation layer can be further increased.

[0056] Next, as shown in FIG. 2(e), the first base material 61 is peeled off from the intermediate laminate, the first adhesive layer 40 is placed on the peeled surface (surface of the first retardation layer 21), and a polarizing plate is attached via the first adhesive layer 40. Since the polarizing plate can be produced by any appropriate method, a detailed description of the manufacturing method of the polarizing plate is omitted. In practice, as shown in FIG. 2(f), the second base material 62 is peeled off and the second adhesive layer 50 is placed on the peeled surface (surface of the second retardation layer 22). For example, the second adhesive layer is formed on a release film (not shown), and a laminate of the second adhesive layer and the release film is arranged so that the second adhesive layer is in contact with the surface of the second retardation layer. In this way, a retardation layer-attached polarizing plate can be produced. When using the retardation layer-attached polarizing plate, the release film is removed.

[0057] G. Image display device The retardation layer-attached polarizing plate described in the above items A to F can be applied to an image display device. Therefore, the embodiment of the present invention includes an image device using such a retardation layer-attached polarizing plate. The image display device according to the embodiment of the present invention typically includes the retardation layer-attached polarizing plate described in the above items A to F on the viewing side. The retardation layer-attached polarizing plate is laminated so that the retardation layer faces the image display panel side (so that the polarizing plate faces the viewing side). Representative examples of the image display device include a liquid crystal display device, an organic electroluminescence (EL) display device, and an inorganic EL display device. In one embodiment, the image display device (for example, an organic EL display device) has a curved shape (substantially a curved display screen) and / or can be bent or folded. EXAMPLES

[0058] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0059] (1) Curing shrinkage rate The cure shrinkage of the ultraviolet curing adhesives used in the examples and comparative examples was measured using a resin cure shrinkage stress measuring device "EU201" manufactured by Sentech Co., Ltd. (2) Phase difference increase The in-plane retardation of the first retardation layer (before the intermediate laminate was prepared) and the intermediate laminate (after annealing if annealing was performed) prepared in the examples and comparative examples was measured using a retardation measuring device manufactured by Axometrics (product name "Axo Scan"). The measurement wavelength of the in-plane retardation was 550 nm, and the measurement temperature was 23°C. The difference between the in-plane retardation of the intermediate laminate and the in-plane retardation of the first retardation layer before the intermediate laminate was prepared was taken as the "retardation increase value". Note that the in-plane retardation of the intermediate laminate is essentially the in-plane retardation of the first retardation layer in the laminate. (3)Δa * b * The polarizing plates with a retardation layer obtained in the examples and comparative examples were attached to a non-alkali glass plate to prepare test samples. The test samples were subjected to a durability test at 80°C for 500 hours. The test samples before and after the durability test were placed on a mirror plate, and the a and b values ​​were measured using a spectrophotometer / colorimeter "CM-26d" manufactured by Konica Minolta, Inc., and the difference between them was defined as Δa * b * It was decided.

[0060] [Production Examples 1 to 4: Preparation of UV-curable adhesives A to D] The components shown in Table 1 were mixed in the ratios shown in Table 1 to prepare ultraviolet-curable adhesives A to D. The cure shrinkage rates of the ultraviolet-curable adhesives A to D were as shown in Table 1. The meanings of the terms shown in Table 1 are as follows: ACMO: Acryloylmorpholine manufactured by KJ Chemicals Plaxel FA1DDM: Unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone manufactured by Daicel Corporation ISTA: Isostearyl acrylate manufactured by Osaka Organic Chemical Industry Co., Ltd. Light Acrylate LA: Lauryl acrylate manufactured by Kyoeisha Chemical Co., Ltd. Light Acrylate 14EG-A: Polyethylene glycol diacrylate manufactured by Kyoeisha Chemical Co., Ltd. Light Acrylate TMP-A: Trimethylpropane triacrylate manufactured by Kyoeisha Chemical Co., Ltd. Aronix M930: Glycerin triacrylate manufactured by Toagosei Co., Ltd. KBM-403: 3-glycidoxypropyltrimethoxysilane manufactured by Shin-Etsu Chemical Co., Ltd. EX-146: p-tert-butylphenyl glycidyl ether manufactured by Nagase ChemteX Corporation OXT-212: 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane manufactured by Toagosei Co., Ltd. OXT-221: 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane manufactured by Toagosei Co., Ltd. ARUFON UP-1190: Manufactured by Toagosei ARUFON UG-4010: Manufactured by Toagosei Omnirad 819: manufactured by IGMresins CPI-110P: San-Apro

[0061] [Table 1]

[0062] [Example 1] 1. Preparation of Polarizer The thermoplastic resin substrate was a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizing film would be the desired value (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5.0 wt %) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%. In this manner, a polarizer having a thickness of 5 μm was formed on the resin substrate.

[0063] 2. Preparation of Polarizing Plates An HC-COP film was attached to the polarizer surface of the resin substrate / polarizer laminate obtained above via an ultraviolet-curable adhesive. Specifically, the curable adhesive was applied to a thickness of 1.0 μm, and the layers were attached using a rolling machine. Then, UV rays were irradiated from the HC-TAC film side to cure the adhesive. The HC-COP film was a film in which a hard coat (HC) layer (thickness 2 μm) was formed on a cyclic olefin resin (COP) film (thickness 25 μm), and the COP film was attached to the polarizer side. Next, the resin substrate was peeled off, and a TAC film having a Re(550) of about 0 nm to 2 nm was attached to the peeled surface in the same manner as above. In this manner, a polarizing plate was obtained.

[0064] 3. Preparation of liquid crystal alignment layer constituting retardation layer 3-1. First retardation layer 55 parts of the compound represented by formula (I), 25 parts of the compound represented by formula (II), and 20 parts of the compound represented by formula (III) were added to 400 parts of cyclopentanone (CPN), and then the mixture was heated to 60°C and stirred to dissolve. After dissolution was confirmed, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts of p-methoxyphenol (MEHQ) were added and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. On the other hand, a polyimide solution for an alignment film was applied to a TAC substrate by spin coating, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was subjected to rubbing treatment to form an alignment film. The rubbing treatment was performed using a commercially available rubbing device. The polymerizable composition obtained above was applied to the surface of the alignment film by spin coating, and dried for 2 minutes at 100° C. The resulting coating film was cooled to room temperature, and then irradiated with 30 mW / cm 2 of a high-pressure mercury lamp. 2 The liquid crystal alignment layer was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a liquid crystal alignment layer (thickness 4 μm). The in-plane retardation Re(550) of the liquid crystal alignment layer was 130 nm. The Re(450) / Re(550) of the liquid crystal alignment layer was 0.851, and it showed reverse dispersion wavelength characteristics.

[0065] [ka] [ka]

[0066] 3-2. Second retardation layer A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (1) (the numbers 65 and 35 in the formula indicate the mol% of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Then, the coating solution was applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. This liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a second retardation layer (thickness 3 μm) exhibiting a refractive index characteristic of nz>nx=ny on the substrate. [ka]

[0067] 4. Preparation of polarizing plate with retardation layer The first retardation layer and the second retardation layer in each of the laminates obtained in 3-1. and 3-2. above were laminated together via UV adhesive A (thickness 1 μm after curing) to form an intermediate laminate. This intermediate laminate was subjected to annealing treatment at 100° C. for 10 minutes. The TAC base material was peeled off from the annealed intermediate laminate, an acrylic adhesive (thickness 5 μm) was placed on the surface of the first retardation layer, and a polarizing plate was laminated via the acrylic adhesive. At this time, the polarizing plate was laminated so that the TAC film was on the first retardation layer side. Next, the PET base material was peeled off, and a laminate of an acrylic adhesive (thickness 26 μm) / release film was placed on the surface of the second retardation layer. In this way, a retardation layer-attached polarizing plate was produced. The obtained retardation layer-attached polarizing plate was subjected to the evaluation of (3) above. The results are shown in Table 2.

[0068] [Examples 2 to 13 and Comparative Examples 1 to 3] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a UV adhesive shown in Table 2 was used and the intermediate laminate was annealed under the conditions shown in Table 2. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 2. In addition, "none" in the annealing treatment column in Table 2 indicates that the annealing treatment was not performed.

[0069] [Table 2]

[0070] [evaluation] As is clear from Table 2, the retardation layer-attached polarizing plates of the examples of the present invention have a Δa * b * That is, it is understood that the retardation layer-attached polarizing plate of the embodiment of the present invention can realize an image display device in which the change in reflective hue in a high-temperature environment is suppressed. [Industrial Applicability]

[0071] The retardation layer-attached polarizing plate of the present invention is suitably used as an anti-reflection circular polarizing plate for an image display device. [Explanation of symbols]

[0072] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 21 First retardation layer 22 Second retardation layer 30 Adhesive layer 40 First adhesive layer 50 Second adhesive layer 100 Polarizing plate with retardation layer

Claims

1. a polarizing plate including a polarizer and a protective layer on at least one of the polarizers; a first retardation layer disposed on a side opposite to a viewing side of the polarizing plate; and a second retardation layer bonded to the first retardation layer on a side opposite to the polarizing plate via an adhesive layer; The first retardation layer is a retardation layer other than a C plate, and the second retardation layer is a C plate; the adhesive layer is made of an active energy ray curable adhesive, and the cure shrinkage rate of the adhesive is 5% or more; Polarizing plate with retardation layer.

2. The first retardation layer exhibits a refractive index characteristic of nx>ny≧nz, Re(550) is 100 nm to 200 nm, and the relationship of Re(450)<Re(550) is satisfied; The second retardation layer exhibits a refractive index characteristic of nz>nx=ny. The retardation layer-attached polarizing plate according to claim 1 : Here, Re(450) and Re(550) are in-plane retardations measured at 23° C. using light with wavelengths of 450 nm and 550 nm, respectively.

3. 3. The polarizing plate with a retardation layer according to claim 2, wherein the first retardation layer and the second retardation layer are layers in which a liquid crystal compound is aligned and fixed.

4. A method for producing the retardation layer-attached polarizing plate according to claim 1, Forming the first retardation layer on a first base material; forming the second retardation layer on a second substrate; and The first retardation layer of the laminate of the first base material and the first retardation layer and the second retardation layer of the laminate of the second base material and the second retardation layer are bonded together via an active energy ray-curable adhesive to form an intermediate laminate; Including, The curing shrinkage rate of the active energy ray curable adhesive is 5% or more. Manufacturing method.

5. The method according to claim 4 , further comprising increasing Re(550) of the first retardation layer by 0.5 nm or more when forming the intermediate laminate.

6. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .

Citation Information

Patent Citations

  • Adhesive for polarizing plate, polarizing plate, and display device

    JP2016136169A

  • Polarizing plate with optical compensation layer and organic el panel using the same

    JP2019066882A

  • Polarizing plate with phase difference layer and image display device using the same

    JP2020064274A

  • Optical laminate and display apparatus

    WO2019216076A1